Low-level light in combination with metabolic modulators for effective therapy of injured brain - Dong, Tingting (J Cereb Blood Flow Metab, 2015)
Vascular damage occurs frequently at the injured brain causing hypoxia and is associated with poor outcomes in the clinics. We found high levels of glycolysis, reduced adenosine triphosphate generation, and increased formation of reactive oxygen species and apoptosis in neurons under hypoxia. Strikingly, these adverse events were reversed significantly by noninvasive exposure of injured brain to low-level light (LLL). Low-level light illumination sustained the mitochondrial membrane potential, constrained cytochrome c leakage in hypoxic cells, and protected them from apoptosis, underscoring a unique property of LLL. The effect of LLL was further bolstered by combination with metabolic substrates such as pyruvate or lactate both in vivo and in vitro. The combinational treatment retained memory and learning activities of injured mice to a normal level, whereas other treatment displayed partial or severe deficiency in these cognitive functions. In accordance with well-protected learning and memory function, the hippocampal region primarily responsible for learning and memory was completely protected by combination treatment, in marked contrast to the severe loss of hippocampal tissue because of secondary damage in control mice. These data clearly suggest that energy metabolic modulators can additively or synergistically enhance the therapeutic effect of LLL in energy-producing insufficient tissue–like injured brain.